PENERAPAN PRINSIP ETIK KEPALA RUANGAN DALAM PENGAMBILAN KEPUTUSAN DI RUMAH SAKIT MURNI TEGUH SUDIRMAN JAKARTA - Tadayu, Rismawati; Silaen, Harsudianto (STIKes Murni Teguh, 2025)
The head of a room's life is filled with a series of decision making. This activity plays an important role. Because the quality of decisions will determine the effectiveness of the plans prepared. Murni Teguh Sudirman Hospital Jakarta is one of the health service places that contributes to providing health services to the community. Apart from that, the head of the room also often gives the implementing nurse the opportunity to express opinions during discussions regarding the implementation of nursing care for patients. This research aims to see the influence of the leadership style of the head of the room on the application of ethical principles in decision making at the Murni Teguh Sudirman Hospital, Jakarta. The type of research carried out was quantitative research with a descriptive research design with a sample size of 100 nurses. The results of statistical analysis using the square test obtained a p-value = <0.05 and a CI of 95%. The recommendation of this research is that the head of the room can always remind nurses to always apply ethics in decision making.